Zarys tradycji i rozwoju czasopiśmiennictwa regionalistycznego w Wielkopolsce w latach powojennych do 1989 roku - Kowalczyk, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
This paper presents the tradition and development of regionalist periodicals and publications in Wielkopolska from the end of World War II to 1989. The author refers to the rich traditions of this type of publication dating back to the period of Prussian partition and the inter-war period. He indicates the socio-political conditions of regionalist publications in post-war Poland which actually limited its development. He exemplifies the achievements of social and cultural, scientific, and tourist associations as well as state institutions in maintaining regionalist publications from the post-war period to the socio-political transformation of 1989.